Tổng hợp một số dẫn xuất ami của 3alpha-hydroxy-lup-20(29)-en-23,28 với axit amin - Lộc, Trần Văn; Sung, Trần Văn (Vietnam Journal of Chemistry, 2014)
Starting from 3α-hydroxy-lup-20(29)-en-23,28-dioic acid, which is isolated with high yield from the plant Schefflera octophylla (Lour.) Harms (Araliaceae), a series of amide esters and amide acids with amino acids have been synthesized. All the synthesized compounds are new. Their structures were determined by IR, MS and NMR spectroscopic methods.